A revision of the Nearctic species of the genus Halobrecta Thomson, 1858 (Coleoptera: Staphylinidae: Aleocharinae) with notes on some Palaearctic species of the genus - Gusarov, Vladimir I. (Zootaxa, 2004)
The marine littoral genus Halobrecta Thomson, 1858 is redescribed. Descriptions and a key to species known from the Nearctic Region (Ha. algophila (Fenyes, 1909) and Ha. flavipes Thomson, 1861) are provided. Atheta barbarae Casey, 1910 and At. importuna Casey, 1911 are placed in synonymy with Halobrecta algophila (Fenyes, 1909). Atheta pocahontas Casey, 1910, At. vaticina Casey, 1910 and Aloconota incertula Casey, 1910 are synonymized with Halobrecta flavipes Thomson, 1861. Lectotypes are designated for Homalota puncticeps Thomson, 1852, Halobrecta flavipes Thomson, 1861, Atheta algophila Fenyes, 1909, At. pocahontas Casey, 1910, At. vaticina Casey, 1910, Aloconota incertula Casey, 1910 and At. importuna Casey, 1911.